Association of Consumption of Non-fermented and Fermented Soy Foods with Obesity in Korean Adults: Analysis of Data from the KoGES-HEXA Study - Bo Hwi Kim; Hye Ran Shin; SuJin Song (Journal of Obesity & Metabolic Syndrome)
Background : This study examined the association of soy foods consumption with obesity in Korean adults. Methods : Data on 131,477 adults (47,828 men and 83,649 women) were selected from the Korean Genome and Epidemiology Study-Health Examinees study. Consumption of soy foods was estimated using a food frequency questionnaire based on classes of non-fermented soy foods or fermented soy paste. General obesity was defined as a body mass index ≥25 kg/m2 and abdominal obesity as a waist circumference ≥90 cm in men and ≥85 cm in women. The association of soy foods consumption with obesity was examined using multiple logistic regression. Results : Greater consumption of non-fermented soy foods was inversely associated with abdominal obesity in both men and women (≥7 servings/week vs. non-consumers: odds ratio [OR], 0.71; 95% confidence interval [CI], 0.57 to 0.87; P for trend=0.001 in men; OR, 0.82; 95% CI, 0.70 to 0.94; P for trend <0.001 in women). Among non-fermented soy foods, higher consumption of legumes was inversely associated with general and abdominal obesity in women. Consumption of tofu or soymilk was inversely associated with obesity in both men and women. Higher consumption of fermented soy paste was associated with a reduced OR for general obesity in men and increased OR for abdominal obesity in women. The inverse association between non-fermented soy foods consumption and obesity was more prominent in postmenopausal women. Conclusion : Greater consumption of non-fermented soy foods is inversely associated with obesity in Korean adults. Further cohort studies are needed to confirm the relationship between soy foods consumption and obesity.